Elevating Sixth-Grade Students' Animal Vocabulary Proficiency Via Quizizz Paper Mode - Damayanti Puspanegara; Dian Fadhilawati (Universitas Tangerang Raya, 2023)
This study is Classroom Action Research aimed at elevating the English vocabulary proficiency of sixth-grade students regarding animals and assessing their perceptions of using Quizizz Paper Mode for vocabulary learning. The research procedure involved four stages: initial planning, implementation, observation and evaluation, and reflection. The study comprises 30 sixth-grade students from SDN Sanankulon 1 Blitar, with a combination of tests and questionnaires used for data collection. The results indicated a significant improvement in students' vocabulary proficiency, demonstrated by a substantial increase in their average scores from 56.10 before the initial action to 87.40 in the post-intervention assessment. Furthermore, questionnaire responses affirmed the positive reception of Quizizz Paper Mode as an effective tool for vocabulary learning, reinforcing the research outcomes. These findings hold promise for educators seeking innovative approaches to enhance vocabulary acquisition among elementary school students, emphasizing the potential of technology-based tools like Quizizz Paper Mode to create engaging and effective learning experiences.